2018
DOI: 10.1038/s41390-018-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of nocturnal hypoxia and an echocardiographic measure of pulmonary hypertension in children with sickle cell disease

Abstract: Our study indicates that NH is associated with PH in C-SCD, and that screening for NH may help to identify C-SCD with higher morbidity risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The intricate pathophysiology of chronic inflammation, increased pulmonary capillary blood volume (PCBV), pulmonary hypertension, and reactive airway disease contribute to the complex progression of SCLD . Worsening of airway resistance in older C‐SCD could be related to SCLD specific etiologies of OAD, like PCBV in addition to asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intricate pathophysiology of chronic inflammation, increased pulmonary capillary blood volume (PCBV), pulmonary hypertension, and reactive airway disease contribute to the complex progression of SCLD . Worsening of airway resistance in older C‐SCD could be related to SCLD specific etiologies of OAD, like PCBV in addition to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted at Penn State Comprehensive Pediatric SCD program, where C-SCD were followed biannually and PFTs were obtained annually. 19 We completed a retrospective chart review of 137 C-SCD and identified 56 children who had been referred to the comprehensive SCD clinic and had completed PFTs on or around the day of their initial comprehensive clinic visit. We identified 36 control subjects from our clinic, who were age and race-matched asthmatic children without SCD.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, nocturnal hypoxia may also be present in several major cardiovascular complications of SCD, including pulmonary hypertension and higher end-diastoclic left ventricular diameters [37]. As per the recommendations [38], children with SCD usually undergo routine echocardiography screening every 1-3 years in the absence of further indication, and in our cohort none of the enrolled patients developed any cardiac complications within the studied period.…”
Section: Discussionmentioning
confidence: 77%
“…Freshly isolated sickle cells were simultaneously incubated in basal medium for 4 h and perfused through the microchannels at a physiological shear stress level of 1 dyne/cm 2 in precisely controlled physiological hypoxia (SpO 2 of 83%) 16 . The SpO 2 level was chosen to be pathologically relevant to SCD, based on clinical studies 46 . Non‐adherent RBCs were washed away and adherent erythrocytes were counted (see details in Supplemental Information).…”
Section: Methodsmentioning
confidence: 99%